2018
DOI: 10.1177/0956797618772504
|View full text |Cite
|
Sign up to set email alerts
|

Collective Narcissism: Americans Exaggerate the Role of Their Home State in Appraising U.S. History

Abstract: Collective narcissism-a phenomenon in which individuals show excessively high regard for their own group-is ubiquitous in studies of small groups. We examined how Americans from the 50 U.S. states ( N = 2,898) remembered U.S. history by asking them, "In terms of percentage, what do you think was your home state's contribution to the history of the United States?" The mean state estimates ranged from 9% (Iowa) to 41% (Virginia), with the total contribution for all states equaling 907%, indicating strong collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(61 citation statements)
references
References 34 publications
(31 reference statements)
3
56
1
Order By: Relevance
“…The concept of collective narcissism extends to the social level of self; the concept of individual narcissism understood as a desire for continual external validation of an inflated self‐view (Crocker & Park, ; Emmons, ; Horney, ; Morf & Rhodewalt, ; Raskin & Terry, ; Rhodewalt & Morf, ; Rhodewalt & Sorrow, ). The concept of collective narcissism is inspired by the literature indicating that the beliefs people hold about themselves (e.g., such as a belief about their self‐worth, that is, self‐esteem, Crocker & Luhtanen, ; Gramzow & Gaertner, ; Luhtanen & Crocker, ; self‐discrepancy, Bizman & Yinon, ; Bizman, Yinon, & Krotman, ; or self‐serving bias, Hornsey, ; Putnam, Ross, Soter, & Roediger, ; Zaromb, Liu, Hanke, Putnam, Roediger III, & Páez, ) have their parallels on the social level of self. As much as people can demand special recognition and privilege for themselves (as individual narcissists do), they can claim the same for the groups they belong to (as collective narcissists do).…”
Section: Concepts Pertaining To Attitudes Towards National Ingroupsmentioning
confidence: 99%
“…The concept of collective narcissism extends to the social level of self; the concept of individual narcissism understood as a desire for continual external validation of an inflated self‐view (Crocker & Park, ; Emmons, ; Horney, ; Morf & Rhodewalt, ; Raskin & Terry, ; Rhodewalt & Morf, ; Rhodewalt & Sorrow, ). The concept of collective narcissism is inspired by the literature indicating that the beliefs people hold about themselves (e.g., such as a belief about their self‐worth, that is, self‐esteem, Crocker & Luhtanen, ; Gramzow & Gaertner, ; Luhtanen & Crocker, ; self‐discrepancy, Bizman & Yinon, ; Bizman, Yinon, & Krotman, ; or self‐serving bias, Hornsey, ; Putnam, Ross, Soter, & Roediger, ; Zaromb, Liu, Hanke, Putnam, Roediger III, & Páez, ) have their parallels on the social level of self. As much as people can demand special recognition and privilege for themselves (as individual narcissists do), they can claim the same for the groups they belong to (as collective narcissists do).…”
Section: Concepts Pertaining To Attitudes Towards National Ingroupsmentioning
confidence: 99%
“…Lewicka refers to this biased perception of place's past as Bhistorical ethnocentric bias^. Recent research has shown that e.g., Americans tend to overestimate the significance of their home state in the U.S. history (Putnam et al 2018), and a similar phenomenon was shown in a study on the perceived contribution of one's home country to world history (Zaromb et al 2018).…”
Section: Introductionmentioning
confidence: 90%
“…Numerous studies have shown that individuals' estimations of their own responsibility for an ingroup's output sums up to more than 100%, which is logically impossible (e.g., Schroeder et al 2016;Thompson and Kelley 1981). Similar biases can apply to collective entities such as ethnic groups or nations, influencing the assessment of the group's role in shaping the history of the community of which they are part: villages, cities, countries, or even the world (Putnam et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…But there are inward forces (the truly -inner voice‖), which must ultimately counterbalance such expectations. Good things come from groupinfluence, such as collective reality monitoring; but it also has bad effects, such as collective narcissism (see Putnam, et al, 2018). Collective memory opens our minds but it can also narrow the scope of what matters to us, depending on the type of biases and quality of reality monitoring of the memory-culture of a group.…”
Section: The Accuracy and Personal Value Of Memorymentioning
confidence: 99%